REKONSTRUKSI STRUKTUR GEOLOGI DAERAH SUPIORI TIMUR – SELATAN, KABUPATEN SUPIORI, PULAU BIAK, PAPUA - Fadlillah Rumanda; Wahju Krisna Hidajat; Fahrudin Fahrudin; Joko Wahyudiono (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Papua and Papua New Guinea are had geology condition are very complex involving interaction between two plates, the Australian Plate and the Pacific Plate. New Guinea formed the result of the movement of oblique convergence (convergence oblique). The products of convergence are shrinkage and formed strike-slip structures and subduction which occur in Papua on 10 Ma. Sorendiweri Strait seen horizontal and vertical fault motion that separated the Biak Island and Supiori Island thar can be identified with the alignment on the satellite image.The purpose of this study was to determine the geological conditions in the study area, the pattern of structures, the main stress that formed the geological structure and reconstruct of geological structures in the study area. The Field research methods are field observation on Supiori track. Record the characteristics of the rock on each formation, measurement of geological structures such as bedding plane, joint and fault plane. Analysis methods such as analysis of alignment manually and visually interpreted on a satellite image DSM (Digital Surface Map). Stereographic analysis of geological structures, combining field data and analysis of alignment to determine the type of structure zone with rotated stress analysis and subsidiary structures method.Geological conditions consist of Oligocene clastic limestone Wainukendi Formation. and Miocene non-clastic limestones Wafordori Formation. Pattern geological structure on Wainukendi Formation., NE-SW normal faults, WSW-ENE strike-slip faults and NE-SW thrust fault. Wafordori Formation., NE-SW normal faults, NE-SW thrust fault. N-S trending major stress is the main primary stress, NE-SW and NW-SE sharpness trending are local stress. Reconstruction of geological structures of the study area began with N-S primary stress that formed E-W Maru reverse fault, NE-SW Soren sinisral fault and NW-SE Maruu, Yondonkir, Maryadori, Biniki dextral fault. The NE-SW trending secondary stress formed NW-SE Kepudari thrust fault, Yon reverse fault and Donkir reverse fault at south of the study area.